Ciudad y rebeldía - Zamudio Tobar, Gladys; Avellaneda Báez, Raúl; Bejarano, Alberto; Rojas Miranda, Juan Sebastián; Rojas Miranda, María Camila; Vivas Betancourt, Angélica María; Giraldo, Germán; Sánchez Borrero, Ana Milena; Marroquín, Juan Pablo (Universidad Santiago de Cali, 2022)
Published